Mental Health Care Experiences in Prehospital and Community Settings: A Scoping Review - Mahato, Preeti; Rolfe, Ursula (Europasian Journal of Medical Sciences, 2023)
Background Mental health issues are among the top ten causes of disease burden worldwide. Many people waiting for mental health treatment are being resorted to emergency or crisis services and evidence points to low levels of satisfaction with these services. The purpose of this scoping review is therefore to explore the experiences of mental health patients accessing prehospital settings, for example emergency care through ambulance use and emergency medical services, and community care. Data and Methods To identify a knowledge gap and sources of evidence, a scoping review was conducted that examined research about the experiences of people accessing prehospital and community care. A scoping review using a systematic and comprehensive literature search of databases resulted in the inclusion of 10 articles. These articles were synthesised using thematic analysis and resulted in five different themes related to access of community and prehospital based sources. Results The themes identified were: (i) communication; (ii) relationship with patients and family members; (iii) attitude of providers and trust established; (iv) care and support; and (iv) satisfaction. Some themes overlap and were interrelated. For example, attitudes of healthcare staff determined the type of communication with patients: either positive or negative. In turn, communication by healthcare staff also affected the relationship formed with the patients and the trust established with them. In addition, results of quantitative studies were presented separately. Conclusion The review identified that mental health service users accessing prehospital and community-based services are seeking support because of dissatisfaction with immediacy of responses elsewhere. To meet this increased demand, paramedics need further education and support on mental health to ensure the appropriate care of these service users.